Development of N-class potassium nitrate - sorbitol solid propellant rocket motor / Mohamad Amirul Muhammad - Muhammad, Mohamad Amirul (2023)
In the age of Internet of Things (IoT), satellite launching has become more common than for the past decades. To date, rocket system is the only means of bringing satellites into Earth’s orbit. However, the technology is very localized, and Malaysia is still in an embryonic stage. In this thesis, the study of solid rocket motor (SRM) using sugar-based propellant is documented. The main motivation is to produce a reliable SRM using a relatively cheap and easily available resources since the commonly built high power rocket are made from expensive and hardly obtained materials. The propellant fabrication was studied using several casting methods with target of obtaining density ratio of more than 95 %, the study of SRM case was done using Ansys static structural analysis by first verifying the setup with exact mathematical solution and used the setup to obtain the maximum von-Mises stress to calculate the safety factor of the SRM case. The rocket motor was designed to produce a total impulse of N-class motor, which is mainly developed for sounding rocket. The focus of the study is on the propellant formulation, design and fabrication of the SRM case, and performance assessment of the SRM through static test. Results showed that there is three propellant casting method that produced a density ratio of more than the threshold value of 95 %. Furthermore, the analysis of SRM case structural integrity revealed maximum stress exceeding the targeted safety factor of 1.5 by 35 %. The static firing test performance was able to be recorded and plotted in a force against time graph with calculated total impulse of lower than design due to nozzle ejection event that occurs. However, the test has provided some insights into the SRM performance, although the combustion has prematurely ended due to nozzle ejection. A detail cause and effect analysis are presented for future improvement. In short, three casting methods was found to produce propellant with higher density ratio than the target of 95%and the SRM was assets to have higher than target safety factor of 1.5. The SRM performance also has been verify in term of force and total impulse produced.